2016
DOI: 10.1097/jom.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Employer Productivity Metrics to Lost Productivity Estimated by Commonly Used Questionnaires

Abstract: Objective To assess construct and discriminant validity of four health-related work productivity loss questionnaires in relation to employer productivity metrics, and to describe variation in economic estimates of productivity loss provided by the questionnaires in healthy workers. Methods 58 billing office workers completed surveys including health information and four productivity loss questionnaires. Employer productivity metrics and work hours were also obtained. Results Productivity loss questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Furthermore, because the work performance level of the participants in this study was generally high (i.e. 7.7 on a scale from 0-10) (de Vries et al 2012), this might have resulted in a ceiling effect, which is known to occur when using the WHO-HPQ to measure work performance in a relatively healthy population (Gardner et al 2016). Consequently, due to the possible lack of variability (Garin 2014), it may have been difficult to find differences between shift and non-shift workers.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, because the work performance level of the participants in this study was generally high (i.e. 7.7 on a scale from 0-10) (de Vries et al 2012), this might have resulted in a ceiling effect, which is known to occur when using the WHO-HPQ to measure work performance in a relatively healthy population (Gardner et al 2016). Consequently, due to the possible lack of variability (Garin 2014), it may have been difficult to find differences between shift and non-shift workers.…”
Section: Discussionmentioning
confidence: 95%
“…Measures that in this way could improve the quality of care for patients with depression and poor work ability thus could facilitate return to work and have a significant effect on the rehabilitation process. Even if there are studies that show the relation between work ability and productivity loss there is a lack and need of more studies, studying possible correlation between work ability index (WAI)-score and productivity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of 21 health-related productivity measures did not identify a valid gold standard (14). In a recent study of commonly used productivity loss questionnaires, it was reported that these measures had only weak to moderate correlations with worker performance indicators used by employers (19). Schwartz and Riedel (20) suggested moving away from the search for a gold standard and that reasonable instruments with characteristics meeting the main requirements of measurement aims do currently exist.…”
Section: Results Of Seemingly Unrelated Regression Models For Incremementioning
confidence: 99%
“…Thirdly, the usage of the employer's perspective does not account for participants making up for missed work days with overtime on other days, which could have potentially biased absenteeism findings to higher levels. Another study limitation concerns the presenteeism measure used.The presenteeism section of the HPQ is not health-specific, is a general view of reduced at-work performance, and not sensitive in the detection of differing health states (19). This means that the results obtained may potentially overestimate actual presenteeism (190).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation